Increased symmetric dimethyl-arginine is a predictor factor of decreased platelet reactivity and increased bleeding risk in patients with acute coronary syndrome. (14th October 2021) - Eyileten, C; Jarosz-Popek, J; Jakubik, D; Gasecka, A; Wolska, M; Czajka, P; Nowak, A; Ufnal, M; Dizdarevic, A; Toma, A; Lang, I; Postula, M; et al.
Abstract: Background: One of the promising biomarkers in CVD are asymmetric dimethylarginine (ADMA) and symmetric dimethylarginine (SDMA), which are products of L-arginine methylation and are both involved in endothelial dysfunction. ADMA, SDMA and L-homoarginine, have emerged as biomarkers linked to cardiovascular outcomes [1]. Purpose: To investigate the association of SDMA with platelet reactivity and bleeding risk in patients with acute coronary syndrome (ACS) treated with potent P2Y12 inhibitors prasugrel and ticagrelor. Methods: Our prospective observational study enrolled 292 patients with ACS undergoing percuteneus coronary intervention [2]. Plasma concentrations of SDMA were measured during the hospitalization for ACS. Impedance aggregometry was used. The primary study endpoint was the concentration of metabolites and platelet reactivity. The primary clinical outcome endpoint was the incidence of Thrombolysis in Myocardial Infarction (TIMI) bleeding events (major, minor and minimal). The efficacy endpoint was the composite of major adverse cardiac events (MACE: stent thrombosis, myocardial infarction, stroke and cardiac death). Results: There was an inverse correlation between SDMA serum levels and platelet reactivity (r=−0.25; p<0.000). The ADP+PGE1-induced platelet reactivity was 33% lower among patients with the highest SDMA quartile (4th) as compared to those with the 1–3rd SDMA quartile (8 [0–29] vs 12 [0–126] U; p<0.001). The AA-induced platelet reactivity was 56% lower among patients with the highest SDMA quartile (4th) as compared to those with the 1–3rd SDMA quartile (4 [0–48] vs 9 [0–133]; p<0.001). In a multivariate model, the highest SDMA (4th) quartile was found to be an independent predictor of the lowest ADP+PGE1 and AA induced platelet aggregation (OR: 2.666, 95% CI [1.184–5.999], p=0.018). Conclusions: Our study shows that high plasma concentration of SDMA, but not ADMA, is independently associated with low platelet reactivity to ADP and AA and is associated with major and minor bleeding events in patients with ACS on potent antiplatelet therapies. Therefore, SDMA might have a potential to be further evaluated as a blood biomarker for individualization of duration and potency of antiplatelet therapies in an ACS population at high risk of bleeding complications. Acknowledgment: I-COMET research team FUNDunding Acknowledgement: Type of funding sources: None.